Association between proton pump inhibitors and severe hematological toxicity in patients receiving pemetrexed-based anticancer treatment: The prospective IPPEM study. (April 2022) - Slimano, Florian; Le Bozec, Antoine; Cransac, Amélie; Foucher, Pascal; Lesauvage, François; Delclaux, Bertrand; Dory, Anne; Mennecier, Bertrand; Bertrand, Benjamin; Gubeno-Dumon, Marie-Christine; Dukic, Sylvain; Mongaret, Céline; et al.
Highlight: Hematological toxicity of pemetrexed is more severe with PPI use. Clinical consequences of pemetrexed toxicity are more frequent with PPI use. When starting pemetrexed, PPI should be deprescribed when possible. Abstract: Objective: Pemetrexed is associated with hematological toxicity. Drug-drug interactions (DDIs) between methotrexate and proton pump inhibitors (PPIs) induce a higher risk of hematological toxicity due to the inhibition of methotrexate excretion by PPIs. As pemetrexed and methotrexate are both excreted by human organic anion transporter 3 (hOAT3), this study investigates the hypothetical DDI between pemetrexed and PPIs in lung cancer patients. The primary objective was the occurrence of severe (grade ≥ 3) hematological toxicity. The secondary objectives were to describe the type of hematological toxicity and associated clinical consequences (NCT03537833). Materials and Methods: PPI consumption was collected for each patient receiving pemetrexed-based anticancer chemotherapy from May 2018 to October 2020 in a prospective multicentric observational and nonrandomized study. Multivariate Cox regression and propensity score (PS) adjustment, PS matching and inverse weighting on PS (IPTW) methods were used. Results: PPI consumption (55 among 156 included patients) was associated with a significantly higher risk of severe hematological toxicity in the multivariable Cox regression model (hazard ratio HR = 2.51, 95% confidence interval [1.47–4.26]; p = 0.005). Similar results were found with PS adjustment (HR = 1.91 CI95% [1.14–3.20]; p = 0.002), PS-matching (HR = 1.93 CI95% [1.08–3.45]; p = 0.02) and IPTW method (HR = 2.06 CI95% [1.27–3.35]; p = 0.004). Severe neutropenia and anemia occurred in 32.7% and 14.1% of patients, respectively. This resulted in 48 anticancer chemotherapy postponements and 24 dose adjustments, 26 growth factor prescriptions, 24 red blood cell transfusions, and 20 hospitalizations. Conclusions: The results strongly suggest an association between PPI consumption and pemetrexed-related severe hematological toxicity. Deprescription of PPIs when feasible should be considered to prevent this DDI.